1988
DOI: 10.1093/chromsci/26.9.443
|View full text |Cite
|
Sign up to set email alerts
|

C18 Solid-Phase Isolation and High-Performance Liquid Chromatography/Ultraviolet Diode Array Determination of Fully Methoxylated Flavones in Citrus Juices

Abstract: A new analytical methodology for the determination of fully methoxylated flavones (FMFs) in citrus juices is described. Isolation of the FMFs is carried out by percolation of 30 mL of clarified citrus juice (to which tetramethyl-o-kaempferol is previously added as internal standard) through a C18 Sep-Pak cartridge, washing with 3 mL of water followed by 5 mL of water/acetonitrile (3:1), and selective elution of the retained FMFs with 5 mL of water/acetonitrile (9:11). Determination of the isolated FMFs is carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 0 publications
4
45
0
1
Order By: Relevance
“…Figure 3 shows a high content in SIN and NOB, a relative low content in HEX, SCU and HEP and a low content in TAN. These results are in agreement with precedent studies on PMF orange juice contents [9][10][11][12].…”
Section: Polymethoxylated Flavone Determination Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Figure 3 shows a high content in SIN and NOB, a relative low content in HEX, SCU and HEP and a low content in TAN. These results are in agreement with precedent studies on PMF orange juice contents [9][10][11][12].…”
Section: Polymethoxylated Flavone Determination Resultssupporting
confidence: 93%
“…PMF Content in orange juice depends of pressing level and the kind extraction process used. Sendra et al [9] have shown that the PMF contents are 10 to 40 fold lower in handly pressing juices (mean of 0.33 mg L -1 ) versus 2.8 to 10.8 mg L -1 in industrial orange juices.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations